Contextualizing the Multimodal Assessment Framework for Junior High School EFL Learners - Jaelani, Alan; Lustyantie, Ninuk; Murtadho, Fathiaty (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the implementation of the Multimodal Assessment Framework (MAF) proposed by Ross et al. (2020) within a junior high school English as a Foreign Language (EFL) classroom. In response to the growing emphasis on multimodal literacy in 21st-century education, the research explores how assessment practices can be reimagined to align with students' diverse meaning-making capacities across visual, verbal, aural, and spatial modes. Using a qualitative case study design, the study involved classroom observations, semi-structured interviews, and the analysis of student-created multimodal artefacts. A rubric adapted from the MAF focusing on four key dimensions: criticality, cultivating creativity, holism, and valuing multimodality was used to evaluate student performance. Findings reveal that the framework enhanced student engagement and creativity, encouraged purposeful use of multimodal resources, and supported inclusive assessment practices. Challenges such as limited teacher familiarity, curriculum constraints, and unequal access to technology emerged. The study reveals the potential of multimodal assessment to foster equitable and meaningful learning in secondary EFL contexts. The results contribute to the growing body of literature on multimodal assessment and offer practical implications for pedagogy and policy in resource-constrained, multilingual educational environments.